2012
DOI: 10.1370/afm.1341
|View full text |Cite
|
Sign up to set email alerts
|

How the Medical Culture Contributes to Coworker-Perpetrated Harassment and Abuse of Family Physicians

Abstract: PURPOSE Harassment and abuse in the workplace of family physicians has been associated with higher levels of stress, increased consumption of alcohol, and higher risk for developing mental health problems. Few studies have examined issues contributing to abusive encounters in the workplace of family physicians. METHODSFor the overall study we used a mixed methods design, which included a cross-sectional survey of a randomly selected sample of active family physicians from the database of the College of Family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…24 25 There is also an indication that medical trainees who were most distressed at the beginning of their training were likely to report continuing stress and distress in the subsequent course of their lives. 26 According to Miedema et al, 27 there are inherent mechanisms that perpetuate abusive behaviour in the medical culture, including working in what is perceived as a stressful environment. This allusion to a view that 'abuse begets abuse' 28 might imply the presence of a cycle of bullying within the medical profession.…”
Section: P269)mentioning
confidence: 99%
“…24 25 There is also an indication that medical trainees who were most distressed at the beginning of their training were likely to report continuing stress and distress in the subsequent course of their lives. 26 According to Miedema et al, 27 there are inherent mechanisms that perpetuate abusive behaviour in the medical culture, including working in what is perceived as a stressful environment. This allusion to a view that 'abuse begets abuse' 28 might imply the presence of a cycle of bullying within the medical profession.…”
Section: P269)mentioning
confidence: 99%
“…It may also result in absences, physical problems, quitting or refusing to work in highrisk areas, and compromised patient care. 5 In the Canadian survey, three-quarters of those who had an abusive encounter in the previous month did not seek help, and 64% did not report the incident. 2 More than half were not aware of any policies to protect them.…”
mentioning
confidence: 98%
“…Canadian physicians working in hospital and psychiatric emergency departments, and after-hours clinics have an increased chance of an abusive encounter, as do clinicians making house calls and those who treat large numbers of patients with mental illness and addiction problems. 5 A survey of about 700 family physicians in the United Kingdom reported that female and male doctors are at equal risk. 6 However, it is not known if the same holds true in Canada.…”
mentioning
confidence: 99%
“…An in-depth study of family physicians in Canada uncovers elements of the workplace culture that appear to contribute to work related harassment and abuse. 11 The authors identify the training period as a critical time to interrupt cultural cycles that perpetuate harassment and abuse.…”
Section: Promising Policies To Stay Ahead Of Speedily Shifting Societmentioning
confidence: 99%